Analisis Kredit Macet pada KPN Satya Bakti Kecamatan Jembrana Kabupaten Jembrana - KUSUMA, KOMANG ANDRI SURYANI; USTRIYANA, I NYOMAN GEDE; WULANDIRA SDJ, A.A.A. (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.5, No.1, Januari 2016, 2016)
Abstract Analysis Of  Bad Loans KPN Satya Bakti At Jembrana Subdistrict, Jembrana Regency Cooperatives are business entities formed in the course based on the principles of cooperatives is based on kinship. Koperasi Pegawai Negeri Satya Bakti is one type of a cooperative whose members are specifically for public servants in support of economic activity. This study aims to determine lending procedures at Koperasi Pegawai Negeri Satya Bakti, the cause of the bad loans to Koperasi Pegawai Negeri Satya Bakti, how to cope with bad loans to Koperasi Pegawai Negeri Satya Bakti. The location of this research selected by purposive sampling. Data used in this study is qualitative data and quantitative data. The results showed that the procedure is performed by Koperasi Pegawai Negeri Satya Bakti start from the loan application, analysis or assessment of credit, credit decision, and disbursement and loan administration. Causes that arise as a result of the bad debt occurred in Koperasi Pegawai Negeri Satya Bakti that is from internal and external problems. Efforts made by the Koperasi Pegawai Negara Satya Bakti in resolving the credit is credit analysis selective, control of bad debts with rescheduling (rescheduling), approach to the debtor with communicate by telephone or orally, using a warning letter I, II, and III to the debtor, kinship approach to debtor by visiting home of debtor directly and the last is  deletion or removed. Keywords : cooperatives, credit, bad loans